Associations of Income and Wealth with Health Status in the Korean Elderly - Park, Bo-Hyun; Jung, Minsoo; Lee, Tae-Jin (Journal of preventive medicine and public health, 2009)
This study aimed to verify the association between wealth or income level and health status after adjusting for other socio-economic position (SEP) indicators among Korean adults aged 45 and over. Data were obtained from the 1st wave of Korean Longitudinal Study of Ageing (households: 6,171, persons: 10,254). We used self-rated health status and activities of daily living (ADLs) as dependent variables. Explanatory variables included both net wealth measured by savings, immovables, the other valuated assets and total income including pay, transfer, property and so on. Binary logistic regression was conducted to examine the relationships. Also, in order to determine the relative health inequality across economic groups, we estimated the relative index of inequality (RII). The inequality of health status was evident among various wealth and income groups. The wealthiest group (5th quintile) was much healthier than the poorest group, and this differential increased with age. Likewise, higher income was associated with better health status among the elderly. However, these effects, as measured by the odds ratio and RII, showed that wealth was more important in determining health status of elderly people. This study suggests that economic capability plays a significant role in determining the health status and other health-related problems among the elderly. Particularly, our results show that health status of the aged is related more closely to the individual's wealth than income.